Building Integrated Photovoltaic Market trend and its Applications - M Tripathy; P K Sadhu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The development of BIPV technology and their implementation in construction of building envelop provides an aesthetical, economical and technical solution. This paper presents the building envelope products, and their properties. BIPV products for pitched roof, flat and curved roof, transparent and semi-transparent facades and skylights have been highlighted in the paper. The properties of BIPV products include solar cell efficiency, open circuit voltage, and short circuit current, maximum power and fill factor. Few successful worldwide existing BIPV Projects with different product categories are also listed in a tabular form. The major considerations for a successful project are proper orientation of BIPV module, suitable distance between buildings, avoidance shadow effects and suitable architectural considerations BIPV technology is a sustainable and cost effective method and the future of this technology is promising as it creates zero energy and zero emission buildings. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7338